2023
DOI: 10.21203/rs.3.rs-2648482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precision spectroscopy and laser cooling scheme of a radium-containing molecule

Abstract: Molecules containing heavy, radioactive nuclei are predicted to be extremely sensitive to violations of the fundamental symmetries of nature. Radium monofluoride molecules are of particular interest, as the nuclear octupole deformation of certain radium isotopes massively boosts their sensitivity to symmetry-violating nuclear properties. Moreover, they are predicted to be laser coolable, opening up a wide range of opportunities for precision studies. Here, we present measurements of the rovibronic structure of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[1][2][3][4] Small molecules containing radioactive elements, e.g., Ra, Ac, or Pa offer sensitive and versatile avenues for precision spectroscopy search of fundamental physics beyond the Standard Model (BSM), including the search of the electron's electric dipole moment (eEDM), nuclear magnetic quadrupole moments (nMQM), and Schiff moments. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Furthermore, Ra(I) in many molecular species has the potential to serve as efficient optical cycling centers 5,16,[22][23][24][25][26][27][28] ; such radium-containing molecules are promising candidates for the application of laser-cooling and subsequent advanced quantum control techniques. High-resolution laser spectroscopy studies of the radium monofluoride (RaF) molecule have recently been reported, 1,[28][29][30] and a laser-cooling scheme has been designed for RaF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] Small molecules containing radioactive elements, e.g., Ra, Ac, or Pa offer sensitive and versatile avenues for precision spectroscopy search of fundamental physics beyond the Standard Model (BSM), including the search of the electron's electric dipole moment (eEDM), nuclear magnetic quadrupole moments (nMQM), and Schiff moments. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Furthermore, Ra(I) in many molecular species has the potential to serve as efficient optical cycling centers 5,16,[22][23][24][25][26][27][28] ; such radium-containing molecules are promising candidates for the application of laser-cooling and subsequent advanced quantum control techniques. High-resolution laser spectroscopy studies of the radium monofluoride (RaF) molecule have recently been reported, 1,[28][29][30] and a laser-cooling scheme has been designed for RaF.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Furthermore, Ra(I) in many molecular species has the potential to serve as efficient optical cycling centers 5,16,[22][23][24][25][26][27][28] ; such radium-containing molecules are promising candidates for the application of laser-cooling and subsequent advanced quantum control techniques. High-resolution laser spectroscopy studies of the radium monofluoride (RaF) molecule have recently been reported, 1,[28][29][30] and a laser-cooling scheme has been designed for RaF. 28 Optical mass spectroscopy detection of radium-containing molecular cations including RaOH + and RaOCH 3 + has also been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation